2016
DOI: 10.17576/mjas-2016-2004-23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fuel Concentrations, Catalyst Loadings and Activation on the Performance of Direct Formic Acid Fuel Cell (Dfafc) Stack

Abstract: An air-breathing stack for a direct formic acid fuel cell (DFAFC) was designed, fabricated and evaluated. The DFAFC stack consisted of six cells arranged in a hexagonal arrangement and each single cell contained a pair of stainless steel current collectors, a membrane electrode assembly (MEA) and a cathode end-plate. A fuel reservoir was located at the center which supplied formic acid supply to the anode of each cell. The effects of fuel concentration, palladium (Pd) loading at the anode and activation on DFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The theoretical open-circuit voltage (OCV) of DFAFC (1.45 V) is higher than that of proton exchange membrane fuel cell (PEMFC) (1.23 V) and direct methanol fuel cell (DMFC) (1.21 V) [6,7]. Formic acid exhibits lower fuel crossover through the Nafion membrane, which allows the use at higher fuel concentration up to 20 M, compared with only 2 M in methanol [8,9]. The reduction of fuel crossover is caused by the repulsion between formate ions in formic acid and sulfuric group in the surface of Nafion membrane [10].…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical open-circuit voltage (OCV) of DFAFC (1.45 V) is higher than that of proton exchange membrane fuel cell (PEMFC) (1.23 V) and direct methanol fuel cell (DMFC) (1.21 V) [6,7]. Formic acid exhibits lower fuel crossover through the Nafion membrane, which allows the use at higher fuel concentration up to 20 M, compared with only 2 M in methanol [8,9]. The reduction of fuel crossover is caused by the repulsion between formate ions in formic acid and sulfuric group in the surface of Nafion membrane [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the catalyst morphology optimization may lead to increasing electrochemically available surface, specific activity of the metal nanoparticles, and power density [44,45].…”
Section: Introductionmentioning
confidence: 99%